Deliberation, Democracy, and the Digital Landscape. (February 2021) - Chambers, Simone; Gastil, John
Deliberative scholarship is particularly well positioned to offer insight on our new digital reality. The papers in this Special Issue showcase both the methodological pluralism that flourishes in deliberative democracy studies and the productive collaborations across methodologies. This Special Issue shows how deliberative theory can place digital media in a wider theoretical context, sharpen our understanding of the Internet's worst features, and show the way forward to a better design for digital public engagement. Whether online or offline, democracy will always remain a work in progress, and these essays should help us navigate a course toward a more deliberative democracy in the digital age.